Pelatihan Dasar Teknik Pengelasan SMAW Bagi Santri Pondok Pesantren Quantum Idea - Komarudin Komarudin; Marysca Shyntia Dewi; Amin Tahmid (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This community service program aimed to improve vocational competence and occupational safety awareness among students of Quantum Idea Islamic Boarding School, Bekasi, through basic Shielded Metal Arc Welding (SMAW) training. The program used a participatory practice-based method consisting of needs observation, activity socialization, theoretical instruction, guided welding practice, mentoring, and evaluation. The training materials covered basic SMAW concepts, welding equipment, electrodes, current setting, personal protective equipment, and basic occupational health and safety procedures. The results showed that the participants understood the basic stages of SMAW welding, recognized welding hazards, applied personal protective equipment more consistently, and performed basic welding practice in 1F and 2F positions under instructor supervision. The mentoring process also encouraged students to view welding skills as a practical competence for facility maintenance and small-scale entrepreneurship in the pesantren environment.